Investigating the Academic Response to Cryptocurrencies: Insights from Research Diversification as Separated by Journal Ranking - Corbet, S.; Oxley, Leslie (2023)
This study provides an in-depth analysis of cryptocurrency research, examining the trends, geographical distribution, and future research directions within this rapidly evolving field. Using a comprehensive dataset, we consider whether such research varies by journal ranking. Our findings reveal a significant increase in the number of publications on cryptocurrencies and blockchain technology from pre-2019 to 2022, with a growing interest in diverse digital assets and related concepts. When considering cryptocurrency-based research, we identify prominent keywords such as “Security,” “Return,” “Investor,” “Risk,” “Volatility,” “COVID,” and “Ethereum,” highlighting the ongoing concerns and interests of researchers in this field. The geographical distribution of author affiliations reveals the prominent role of China and the United States in contributing to cryptocurrency research, with European countries and emerging economies experiencing substantial growth in their number of publications. Based on these findings, we propose several future research directions, including exploring the role of cryptocurrencies in financial inclusion, addressing cybersecurity and privacy concerns, examining the regulatory landscape, and investigating the environmental impact of digital assets. Our study underscores the importance of a multidisciplinary approach to cryptocurrency research, considering the broad societal impacts and implications of this rapidly developing field.